Stratospheric ice crystals - Goodman, Jindra; Pueschel, R. F.; Snetsinger, K. G.; Verma, S. (1990)
In situ sampling of the crystals is described with a NASA high-altitude aircraft to characterize the presence of ice particles and their role in Antarctic ozone chemistry. A NASA wire impactor was employed to collect the crystals, and the device was modified to permit Formvar crystal replication. The size distributions of the columnar crystals show that at the highest altitude the the smallest crystals are collected. The crystals provide surface area for heterogeneous chemical reactions as well as the removal of moisture and particles from the stratosphere and its ozone-related components.